Accelerated aging behavior and life prediction of low-temperature vulcanizable CR–BIIR blend based encapsulant material for undersea sensors. Issue 9 (November 2021) - Mohanadas, PN; Santhanakrishnan, T; Manoj, NR; Mukundan, T
Blends of chloroprene rubber (CR) and bromobutyl rubber (BIIR) with low-temperature vulcanization (LTV) technology were found suitable for the encapsulation of temperature-sensitive undersea sensors. Polymeric blends are susceptible to the aging process due to external environments such as heat, oxygen, ozone, light, and mechanical stresses, etc. Hence, the longevity of these blends for hostile seawater applications is a great concern. The marine aging of rubber blends was not investigated much. In this study, the LTV blends with a curing system based on lead and zinc oxides were subjected to accelerated aging in a 3.5% aqueous solution of NaCl from 40°C to 70°C. The retention of tensile strength, % elongation and modulus properties were estimated. It was observed that aging could lead to an initial increase in the modulus and a considerable decrease in ultimate tensile strength and elongation values with an increase in the aging period. Reduction in elongation at break showed a gradual decrease with an increase in both temperature and exposure time. It was observed that the blends with lead oxide cure system were prone to more degradation than ZnO-based blend. A life of 6.5 years and 5.3 years at 25°C for blends based on ZnO and lead oxide cure systems was estimated. The water diffusion coefficient was found to be of the order of 10 −12 mm 2 s −1 for both blends.